2011
DOI: 10.1002/hed.21791
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between serum thyroglobulin and 18FDG‐PET/CT in 131I‐negative differentiated thyroid carcinomas

Abstract: Although (18) FDG-PET/CT scans are more likely to be positive with pretest Tg levels ≥4.6 ng/mL, 11% of patients with DTC with a lower serum Tg level will still have a positive scan. Our findings are in contrast with the American Thyroid Association (ATA) guidelines, which only recommend to perform (18) FDG-PET/CT in patients with Tg levels >10 ng/mL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 20 publications
2
49
0
2
Order By: Relevance
“…The present findings are in agreement with those previously reported by our and other groups suggesting that a cut-off value of 10 ng/mL for unstimulated Tg, as proposed by the American Thyroid Association [7], is a suboptimal criterion for the eligibility of patients requiring 18 [10][11][12][13]. The American Thyroid Association recommendation, however, was principally based on the results obtained by comparing serum Tg levels with 18 F-FDG PET examinations without concurrent CT scanning [19,20].…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…The present findings are in agreement with those previously reported by our and other groups suggesting that a cut-off value of 10 ng/mL for unstimulated Tg, as proposed by the American Thyroid Association [7], is a suboptimal criterion for the eligibility of patients requiring 18 [10][11][12][13]. The American Thyroid Association recommendation, however, was principally based on the results obtained by comparing serum Tg levels with 18 F-FDG PET examinations without concurrent CT scanning [19,20].…”
Section: Discussionsupporting
confidence: 95%
“…Previous studies have shown wide heterogeneity in setting the Tg threshold for optimal accuracy of 18 F-FDG PET/CT scans in patients with DTC [7,[9][10][11][12][13]. More recently, the kinetics of TSH-suppressed Tg have been shown to be a strong prognostic predictor in patients with DTC.…”
Section: Introductionmentioning
confidence: 98%
“…The specificity of PET alone was found to be 50% vs 89% for PET/CT (76). Although serum Tg levels correlate with tumor load and true-positive FDG-PET/CT scans increase as Tg levels increase, several authors have suggested that a cutoff value of 10 ng/ml for unstimulated Tg is at best a suboptimal criteria for the selection of patients for FDG-PET/CT (77,78,79). Giovanella et al (77) reported true-positive FDG-PET/CT examinations in 14 of 30 patients (46%) with Tg levels of !10 ng/ml, and Vera et al (78) reported FDG-PET/CT positive findings in 20 of 44 DTC patients (45%) with Tg levels of !10 ng/ml during LT4 therapy and with negative DxWBS.…”
Section: Controversies and Areas Of Uncertaintymentioning
confidence: 99%
“…For this reason, lower thresholds have been proposed. Giovanella et al, for example, suggested a level of 4.6 ng/mL, which was associated with a sensitivity of 96% (110). Based on a subsequent analysis of 102 cases, the same investigators also demonstrated that 18 FDG-PET positivity is predicted by a serum thyroglobulin doubling time of less than 1 year, regardless of the Tg level itself (111).…”
Section: European Journal Of Endocrinologymentioning
confidence: 95%